POT IRRIGATION CONTROL THROUGH THE CLIMATOLOGIC SEQUENTIAL WATER BALANCE - Silva, Adilson Nunes da; Bortolotto, Rafael Pivotto; Tomaz, Halan Vieira de Queiroz; Reis, LetÃcia Grigolon; Olinda, Ricardo Alves de; Aguila, LÃlia Sichmann Heiffig-del; Reichardt, Klaus (REVISTA DE AGRICULTURA, 2013)
Ratings of crop behavior under different soil water conditions are very important to improve agricultural management, a difficult task to be carried outÂ in greenhouses due to the lack of simple methodologies ofÂ low cost and of easy implementation. This article evaluates the efficiency of using a computational program of Sequential Water Balance, to study the response of the Jatropha curcas crop under different irrigation levels. Pots of large size (1.0 m high and 0.3 m in diameter), difficult to be weighed, were used in a greenhouse, from June to December 2009, in Piracicaba, SP, Brazil, with plantsÂ grown in a substrate of 50% sandy soil and 50% cured manure. The experimental design consisted of randomized blocks with treatments corresponding to water depths of 100%, 75% and 50% of the maximum available water capacity (AWC), with 16 replicates. Measuring only air temperature and knowing substrate AWC it was possible to control the soil water conditions over the whole experimental period, which were checked at the end of the experiment. Data indicate that this simple method that avoids weighing heavy containers in large number is very suitable for water control in pots arranged in a greenhouse.